Dentoalveolar Biprotrusion treatment of class I and class II skeletal angle in teen. - Gallardo Moreno , Wenceslao (Revista Universidad de Guayaquil, 2013)
This report describes a brunette girl , 11 years 7 months old , from Guayaquil - Ecuador who had severe bimaxillary dento -alveolar protrusion , diastemas and labial deficiency. The treatment approach to her problems was through the extraction of the four first premolars and retraction of the anterior teeth. Front and profile facial esthetics and occlusion of the girl significantly improved with treatment, biprotrusion was corrected and there was a positive response of the soft tissues and excellent lip closure was achieved. Examining Cephalograms according to Ricketts before and after treatment , the interincisal angle was increased from 106 º to 138 º , the lower incisors in relation to the plane APO + 7 mm was changed to +1 mm , achieving an excellent lip closure and a good relationship between the aesthetic level , nose - chin and lips. The lower lip which was + 6 in relation to the aesthetic level , improved noticeably , reaching a – 1 aesthetic level . The treatment lasted 29 months , clinically discrepancy between RC and OC is not evident, there are no symptoms in the TMJ , the result is stable ( fixed retainer between canines and superior incisors ) and the prognosis, excellent . The third molars are in mouth and functioning normally. . Post treatment records after several years, showed excellent results with a good occlusion and long term stability.
Keywords: Angle Class I; bialveolar protrusión; bimaxillary dentoalveolar protrusión; protrusion of the lips; convex facial profile